Influence of celebrity endorsement and digital marketing on youth purchasing decisions: a comparative study of Ikorodu area - Yusuf Ismaila, Mustapha (2022)
The continuous increase in the population of Nigeria, especially the youthful population characterized by innovative and dynamic needs, necessitates business firms to adopt opposite programmes and strategies to meet the needs of this segment of the market. Therefore, this study examined the influence of celebrity endorsement and digital marketing on youth purchasing decisions. The study utilized primary sources to gather the required data, and a sample size of 397, consisting of youths between the age of 15-35 years residing in Ikorodu L.G.A. was selected from the study’s population. Pearson moment correlation was used to test the formulated hypotheses, and the data was analyzed through the aid of SPSS version 23. The study finding revealed that source trustworthiness influences youth purchasing decisions more than social media engagement. More so, online reachability influences youth purchasing decisions than source alignment and that digital campaign has more effect on the youth purchasing decisions than source attractiveness. It was concluded that digital marketing has more effect on youth purchasing decisions than a celebrity endorsement. It was recommended that organizations with youthful target audiences adopt more digital marketing strategies as it influenced youth purchasing decisions than a celebrity endorsement.